Different neural activations for an approaching friend versus stranger: Linking personal space to numerical cognition. Issue 6 (27th April 2020) - Rubinsten, Orly; Korem, Nachshon; Perry, Anat; Goldberg, Miri; Shamay‐Tsoory, Simone
Abstract: Introduction: Typically, humans place themselves at a preferred distance from others. This distance is known to characterize human spatial behavior. Here, we focused on neurocognitive conditions that may affect interpersonal distances. The current study investigated whether neurocognitive deficiencies in numerical and spatial knowledge may affect social perception and modulate personal space. Method: In an event‐related potential (ERP) study, university students with developmental dyscalculia (DD) and typically developing control participants were given a computerized version of the comfortable interpersonal distance task, in which participants were instructed to press the spacebar when they began to feel uncomfortable by the approach of a virtual protagonist. Results: Results showed that students with deficiencies in numerical and spatial skills (i.e., DD) demonstrated reduced variability in their preferred distance from an approaching friend. Importantly, DD showed decreased amplitude of the N1 wave in the friend condition. Conclusion: These results suggest that people coping with deficiencies in spatial cognition have a less efficient allocation of spatial attention in the service of processing personal distances. Accordingly, the study highlights the fundamental role of spatial neurocognition in organizing social space. Abstract : We found that even this seemingly resilient group of young adults with dyscalculia who are enrolled in university display abnormal neuro‐physiological functioning suggestive of a less efficient allocation of spatial attention in the service of processing distances in everyday activities. This deficient attention mechanism leads to abnormal choices of preferred distance from others, mainly from friends, which may have an effect on reciprocal social behavior.